2022
DOI: 10.1002/adom.202102426
|View full text |Cite
|
Sign up to set email alerts
|

Emission‐Color‐Tunable Pb−Sn Alloyed Single Crystals with High Luminescent Efficiency and Stability

Abstract: Although multiple emissive materials are of great research interest due to their great potential in a variety of applications, it is still challenging to prepare highly luminescent color‐tunable phosphors. Herein, the authors report a series of Pb−Sn alloyed single crystals, (C10NH22)2Pb1−xSnxBr4 (x = 0 to 1), that are equipped with two independent self‐trapped excitons (STEs) emitters. Multicolor luminescent output from blue to red and white light can be obtained by tailoring the composition, excitation wavel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…† Dual emissions can generally be achieved in Sn 2+based multi-ionic metal halides. 14,42 However, as we know, Sn 2+ -based multi-ionic metal halides are susceptible to the rapid oxidation of Sn 2+ to Sn 4+ . The stability of multi-ionic metal halides is important for their potential applications in light-emitting diodes or anti-counterfeiting.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…† Dual emissions can generally be achieved in Sn 2+based multi-ionic metal halides. 14,42 However, as we know, Sn 2+ -based multi-ionic metal halides are susceptible to the rapid oxidation of Sn 2+ to Sn 4+ . The stability of multi-ionic metal halides is important for their potential applications in light-emitting diodes or anti-counterfeiting.…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12][13] Compared to 3D structures, the soft crystal lattices of lowdimensional structures facilitate the self-trapping of excitons in photoinduced transient lattice defects due to strong phononexciton interactions, thus leading to large Stokes shifts and broad luminescence during the relaxation process. [14][15][16] In 2014, Karunadasa et al reported an intriguing broad emission in a lead halide material, (N-MEDA)PbBr 4 (N-MEDA: N1-methyl-ethane-1,2-diammonium). This emission arises from the radiative recombination of self-trapped excitons (STEs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multi-functional luminescent materials with broad response to different excitation sources afford the various applications in the solid-state lighting device, [1][2][3][4][5][6][7][8][9][10][11][12][13] anti-counterfeiting, [14][15][16][17][18][19] optical refrigeration, [20,21] and X-ray detection. [22][23][24][25][26][27][28] Recently, anti-counterfeiting has become a serious global issue in our daily lives, commercial trade, intellectual property protection, document encryption, etc.…”
Section: Introductionmentioning
confidence: 99%
“…[32] Kuang et al recently pointed that there are two independent STEs emitters in Pb−Sn alloyed single crystals, (C 10 NH 22 ) 2 Pb 1−x Sn x Br 4 . [33] In this regard, the photogenerated species in the mixed Pb−Sn perovskite and the formation process of broad emission bands remain controversial. Therefore, more in-depth investigations are required to understand the true origin of the broad light emission in these materials.…”
Section: Introductionmentioning
confidence: 99%